Electroporation-Mediated Immunization of a Candidate DNA Vaccine Expressing Dengue Virus Serotype 4 prM-E Antigen Confers Long-Term Protection in Mice - Sheng, Ziyang (Virol Sin, 2019)
Dengue fever, caused by dengue viruses (DENVs), is a widespread mosquito-borne zoonotic disease; however, there is no available anti-dengue vaccine for worldwide use. In the current study, a DNA vaccine candidate (pV-D4ME) expressing prM-E protein of DENV serotype 4 (DENV-4) was constructed, and its immunogenicity and protection were evaluated in immunocompetent BALB/c mice. The pV-D4ME candidate vaccine induced effective humoral and cellular immunity of mice against DENV-4 in vivo when administered both at 50 μg and 5 μg through electroporation. Two weeks after receiving three immunizations, both doses of pV-D4ME DNA were shown to confer effective protection against lethal DENV-4 challenge. Notably, at 6 months after the three immunizations, 50 μg, but not 5 μg, of pV-D4ME could provide stable protection (100% survival rate) against DENV-4 lethal challenge without any obvious clinical signs. These results suggest that immunization with 50 μg pV-D4ME through electroporation could confer effective and long-term protection against DENV-4, offering a promising approach for development of a novel DNA vaccine against DENVs.